Replication Compartments—The Great Survival Strategy for Epstein–Barr Virus Lytic Replication - Atsuko Sugimoto (Microorganisms, 2022)
During Epstein–Barr virus (EBV) lytic replication, viral DNA synthesis is carried out in viral replication factories called replication compartments (RCs), which are located at discrete sites in the nucleus. Viral proteins constituting the viral replication machinery are accumulated in the RCs to amplify viral genomes. Newly synthesized viral DNA is stored in a subdomain of the RC termed the BMRF1-core, matured by host factors, and finally packed into assembled viral capsids. Late (L) genes are transcribed from DNA stored in the BMRF1-core through a process that is mainly dependent on the viral pre-initiation complex (vPIC). RC formation is a well-regulated system and strongly advantageous for EBV survival because of the following aspects: (1) RCs enable the spatial separation of newly synthesized viral DNA from the cellular chromosome for protection and maturation of viral DNA; (2) EBV-coded proteins and their interaction partners are recruited to RCs, which enhances the interactions among viral proteins, cellular proteins, and viral DNA; (3) the formation of RCs benefits continuous replication, leading to L gene transcription; and (4) DNA storage and maturation leads to efficient progeny viral production. Here, we review the state of knowledge of this important viral structure and discuss its roles in EBV survival.